Pulmonary Atresia (PA) with Anomalous Origin of the Pulmonary Artery (KYAMC Journal, 2023)
Pulmonary atresia with ventricular septal defect is a severe form of congenital cyanotic heart disease (TOF) but its not very common form. Here main pulmonary does not arises from common arterial trunk. In pulmonary atresia there is no proper formation ofthe pulmonary valve which allows blood from the heart to thelung of patient. Instead of opening and closing of the valve,a solid sheet of tissue develops. Therefore blood cannot flow by its normal path to take oxygen from the lung. Instead, inadequate blood travels to the lung through other natural routes within the heart and its arteries and presenting degree of pulmonary atresia or discontinuity in arteries. MDCT gave structural details in this regard. So, role of MDCT play an important role to evaluate the details important information needed in preoperative evaluation for surgical policy in atretic patients. Here we discuss a case of pulmonary atresia (PA) with anomalous origin of the pulmonary artery.KYAMC Journal Vol. 14, No. 02, July 2023: 102-104.